Personalized adjuvant treatment: go through the past to the future - Liu, Si-Yang; Wu, Yi-Long (Journal of Thoracic Disease, 2019)
Thanks for Pro. Roviello, Klevansky and Masago for their interest in ADJUVANT study and appreciate it raises questions about the eventual OS benefits and ctDNA detection for adjuvant TKI treatment in epidermal growth factor receptor (EGFR) mutant patients.